Effects of some factors on the gelation of commercially prepared "Gulaman" bars (Agar-Agar) - De Guzman, Leila T. (1978)
A study on the rate of dissolution of commercially prepared "gulaman" bars showed that a "gulaman" concentration of 4.3% dissolved fastest compared to concentrations of 3.3%, 2.2% and 1.6%. Moreover, using the above concentrations the gelling properties of each sample was determined based on time of gelation, temperature of gelation, viscosity of the sol, rigidity of the gel, temperature of solation and yield. General acceptability ratings of each sample was also taken. The concentration of 4.3% that gave the most desirable appearance and texture was used in the second phase. The second phase included the study of the combined effects of temperature, pH, and percent soluble solids on the gelling properties of "gulaman". The effect of very low pH was not altered inspite of the increase in the amount of soluble solids or cooling the sol at refrigeration temperature of 17 to 20°C. At pH 2, no gelation occurred. At a higher pH, pH 5 and pH 8, gelation took place. The amount of soluble solids, however, affected the rigidity of the gel. At these pH values, the sample with 15% soluble solids were a little more rigid than those with 30% soluble solids. Samples cooled at room temperature and at refrigeration temperature did not differ much in rigidity, although they showed significant results or differences in the time and temperature of gelation. The low temperature atmosphere of the refrigerator promoted faster gelling time and lower gelation temperature.